AUDITORÍA FINANCIERA A LA EMPRESA PROVEEDORA LOJANA DE PRODUCTOS DE CONSUMO MASIVO SAMANIEGO PROLCOM CIA. LTDA. DE LA CIUDAD DE LOJA PERIODO 2016 - Sánchez Juárez, Jessica Antonieta (2018)
The thesis called "Financial Audit to the Loja Provider Company of Mass Consumption Products Samaniego PROLCOM CIA. LTDA., From the city of Loja, Period 2016 ", has been prepared according to the Regulations of Academic Regime of the National University of Loja, as a prerequisite to choose the degree and title of Engineering in Accounting and Auditing, according to compliance of the general and specific objective that are detailed below: The work of Thesis was carried out in compliance with the general objective stated "To carry out the Financial Audit of the Proveedora Lojana company of Mass Consumption Products Samaniego PROLCOM CIA. LTDA., Of the city of Loja, in the 2016 period ", with the purpose of deepening the knowledge in relation to the Financial Audit in the private sector and giving a truthful and reasonable opinion of the balances of the evaluated accounts and that are presented in the financial statements. To evaluate the internal control system of the PROLCOM CIA Company. LTDA., We proceeded to the development of internal control programs and questionnaires in order to determine the weaknesses presented by the company, obtaining a low risk and a high level of confidence, thus reaching to establish the degree of reasonableness of the balances presented. in the Financial Statements, the same ones that were 5 examined by components such as: Assets, Liabilities, Income and Expenses, where it is evident that no surprise transactions are made, the bank reconciliations are not prepared within the determined periods, there is no guarantee and guarantees to the personnel in charge of accounts receivable, does not have a Manual of Functions that helps segregation of functions, no policies have been established for accounts receivable for this reason clients do not cancel within the agreed deadlines affecting the company in its liquidity with payments to suppliers, sales are not recorded daily, information that facilitated the preparation of the narrative, analytical and summary edits, results that allowed the Final Report to be made with their respective conclusions and recommendations. It is concluded that the company PROLCOM CIA. LTDA., After having analyzed and evaluated the internal control system in each of the components, a low level of risk and a high confidence level were determined and that the existing weaknesses should be corrected by the managers and administrative staff. , in order to achieve the goals and objectives proposed..